Modifying Yeast Tolerance to Inhibitory Conditions of Ethanol Production Processes - Caspeta, Luis; Castillo, Tania; Nielsen, Jens (Frontiers in Bioengineering and Biotechnology, 2015)
Saccharomyces cerevisiae strains having a broad range of substrate utilization, rapid substrate consumption and conversion to ethanol, as well as good tolerance to inhibitory conditions are ideal for cost-competitive ethanol production from lignocellulose. A major drawback to directly design S. cerevisiae tolerance to inhibitory conditions of lignocellulosic ethanol production processes is the lack of knowledge about basic aspects of its cellular signaling network in response to stress. Here we highlight the inhibitory conditions found in ethanol production processes, the targeted cellular functions, the key contributions of integrated –omics analysis to reveal cellular stress responses according to these inhibitors, and current status on design-based engineering of tolerant and efficient S. cerevisiae strains for ethanol production from lignocellulose.